Educational Values In Totto-Chan’s Novel “The Little Girl At The Window” And Its Relevance With Learning Literature In High School - Sidik, Ahmad; Setiawati, Eni (Universitas Qamarul Huda Badaruddin, 2022)
This research aimed to describe: 1) the educational values which is contained in Totto-chan’s novel: The Little Girl at the Window by Tetsuko Kuroyanagi; and 2) The relevance of the educational values in Totto-chan’s novel: The Little Girl at the Window by Tetsuko Kuroyanagi for education in Indonesia. Education is a guide in the life of growing children. As for the purpose of education is to guide all the natures that exist in children, so that they are as humans and members of society can achieve the highest safety and happiness (Ki Hadjar Dewantara, an Indonesian Father of education). Education is one of the ways to get a better life both in the world and the hereafter. The researcher is interested in doing the research entitled The Educational Values in Tottochan’s Novel: The Little Girl at the Window by Tetsuko Kuroyanagi. The method of this research is using structural approach and sociological approach. The object of this research is the educational values which are contained in Totto-chan’s Novel: The Little Girl at The Window by Tetsuko Kuroyanagi. The data and source of the data are primary data and secondary data. To collect the data this research uses close reading, selecting the data, searching for secondary data, identification and giving description. To analyze the data this research uses identification, classification, and description. The educational values of the novel are revealed by the characters of the story. Each character has his or her own characteristic in his or her narration. Various experiences happened to the character bring positive values to exemplify. Those positive values are the educational values which the readers can grasp. The values can develop the character’s potency to have spiritual power, self-control, personality, brilliance, morals, and skills which are needed by his self or herself and society. The educational values of the novel are the value of simplicity, independence, mutual respect, responsibility, patience, wisdom, friendship, hardworking and unyielding, and self-maturity.